Conceptualizing the effects of polarization for US foreign policy behavior in international negotiations: revisiting the two-level game - Friedrichs, Gordon (International studies review, 2022)
Polarization has been a prevalent phenomenon in US politics, yet its foreign policy implications remain understudied. A common assumption is that polarization undermines the utilization of United States’ material power via a coherent grand strategy. In this article, I argue that polarization does not make the United States incapable of enacting a foreign policy per se but instead affects US foreign policy conduct, power, and strategy toward international negotiations. The effects of domestic polarization for US foreign policy behavior in international negotiations are best understood via an advanced application of the “two-level game” model, which conceptualizes a state's domestic politics as a determinant factor for the executive branch's approach toward foreign affairs. I identify three effects polarization has on US foreign policy: (1) a sorting effect, which produces homogenous partisan coalitions with divergent foreign policy preferences and inclines the executive to pursue an obstinate international negotiation conduct; (2) a partisan conflict effect, which weakens Congress as a veto player and reduces United States’ bargaining power; and, finally, (3) an institutional corrosion effect, which inclines the executive branch to manipulate domestic support and to politicize international negotiations at home. In sum, domestic polarization increases the opportunity costs for US foreign policy toward international negotiations and contributes to global instability. Anecdotal evidence from US foreign policy over the last decade offers support for these effects, but further empirical research is needed to better understand when they are most impactful and in which combination these effects appear.